1985
DOI: 10.1139/m85-163
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuity of charge on cell wall poles of Bacillus subtilis

Abstract: When cell wall poles of Bacillus subtilis were treated with dilute cationized ferritin, label was found only at discrete patches. Since cationized ferritin binds to negatively charged groups, the pole regions that retain label most likely represent localized surface sites of high electronegativity, indicating that the cell wall of B. subtilis is, at least, partially differentiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…They also bind cations and thus constitute a fraction of the wall-binding capacity (127). From a series of covalent modifications of walls from B. subtilis 168, it was concluded that while both TA and peptidoglycan each contribute sites for binding metal cations, the latter would appear to provide a larger fraction (55,131,324,453). In contrast, Heckels et al (212) found that the WTA provides the larger fraction of anionic binding sites in B. subtilis W23, an organism with poly(Rbo-P) WTA.…”
Section: D-alanyl Esters In the Binding Of Ligandsmentioning
confidence: 99%
“…They also bind cations and thus constitute a fraction of the wall-binding capacity (127). From a series of covalent modifications of walls from B. subtilis 168, it was concluded that while both TA and peptidoglycan each contribute sites for binding metal cations, the latter would appear to provide a larger fraction (55,131,324,453). In contrast, Heckels et al (212) found that the WTA provides the larger fraction of anionic binding sites in B. subtilis W23, an organism with poly(Rbo-P) WTA.…”
Section: D-alanyl Esters In the Binding Of Ligandsmentioning
confidence: 99%
“…Although the ionic polymer is present throughout the wall, there is evidence to show that in B. subtilis a large amount is at the outer surface (1,2,7). This could account for the greater proportion of binding sites there (23). Negatively charged groups are also more densely clustered at the poles than on the cylinder wall, but there appear to be none in the septa (22,23).…”
mentioning
confidence: 98%
“…Sonnenfeld et al (28) reported that dilute solutions of PCF had great affinity for cell surface sites expressing high electronegativity and showed that isolated cell walls of B. subtilis could be partially differentiated by surface charge. Chemical modification of isolated walls indicated that the anionic nature of B. subtilis cell walls was due primarily to the carboxyl groups of muramyl peptides and phosphate groups of teichoic acids (29).…”
mentioning
confidence: 99%